Effect of oxytocin massage on uterine involution in vaginam post partum women in self practice of the salabiah midwife - Hafsah Us; Myrna Lestari AB; Elvieta Elvieta; Mey Elisa Safitri (Science Midwifery, 2023)
Introduction: Uterine involution is a process in which the uterus returns to its pre-pregnancy state weighing about 30 grams. Oxytocin massage is massage on the cervical spine along the cervical spine to the 5th to 6th ribs, for 2-3 minutes. Objective: The aim of the study was to analyze the effect of oxytocin massage on uterine involution in vaginal post partum mothers in the independent midwife practice of Salabiah, Banda Sakti district, Lhokseumawe city. Method: The research design used the Quasy Experimental method with the Non-equivalent Control Group Design approach, two groups (the treatment group and the control group). Total population of 12 post partum mothers. The sample technique used incidental sampling as many as 12 post partum mothers and a control group. Data were analyzed by Mann Whitney test. The Result: The results showed that before oxytocin massage in the treatment group and control group all uterine involutions were normal, after oxytocin massage in the treatment group most of the uterine involutions were normal, while in the control group most of the uterine involutions were abnormal. it was found that there was an effect of oxytocin massage on uterine involution with the results of the Mann Whitney test p = 0.002. Conclusion: The conclusion in this study is for health workers in the Researchers suggest that oxytocin massage can continue to be carried out in providing postnatal services to patients so that the quality of care for postpartum mothers can increase.